2017
DOI: 10.1111/maq.12342
|View full text |Cite
|
Sign up to set email alerts
|

The Work of Inscription: Antenatal Care, Birth Documents, and Shan Migrant Women in Chiang Mai

Abstract: For transnational migrant populations, securing birth documents of newly born children has crucial importance in avoiding statelessness for new generations. Drawing on discussions of sovereignty and political subjectivization, I ask how the fact of birth is constituted in the context of transnational migration. Based on ethnographic data collected from an antenatal clinic in Thailand, this article describes how Shan migrant women from Myanmar (also known as Burma) utilize reproductive health services as a way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Another group of studies looked at the impact of vital registration on migrant populations. In Indonesia [ 22 ], Sierra Leone [ 19 ], and Thailand [ 23 ], authors concluded that birth registration is a pathway to access the education and obtain legal identity documents. As a consequence, it increases the likelihood for those individuals to access better economic opportunities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group of studies looked at the impact of vital registration on migrant populations. In Indonesia [ 22 ], Sierra Leone [ 19 ], and Thailand [ 23 ], authors concluded that birth registration is a pathway to access the education and obtain legal identity documents. As a consequence, it increases the likelihood for those individuals to access better economic opportunities.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, it increases the likelihood for those individuals to access better economic opportunities. In Thailand, it was reported that having a birth certificate gives rights and citizenship to migrant children from Myanmar [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Women described their lived experience being a migrant in Thailand without the proper documentation and wanted greater stability for their children. Another study with Shan migrants in Thailand reported safe birth and acquiring identification documents as motivations for attending antenatal care [15]. Thailand does not provide citizenship to children born in Thailand of migrant parents, but the country's policies to provide elementary education and low-cost healthcare coverage to migrant children may also incentivize birth registration.…”
Section: Top Factorsmentioning
confidence: 99%
“…Anthropologists have examined the power of documents within a range of contexts: as a material tool of bureaucratic ideology (Hull 2012b; Chelcea 2016), as a mediator of migration and citizenship (Chu 2010; Reeves 2013; Seo 2016; Abarca and Coutin 2018), as an instrument of state surveillance (Scott 1985; Torpey 2000), and as a mechanism linking the politics of historical archiving, memory, and lived experience (Tarlo 2003; Stoler 2009). Existing literature reveals a strong tendency to conceptualize documents and the practices that produce them within the analytic frames of bureaucracy and state control (Hull 2012a).…”
Section: The Anthropology Of Documents and The History Of Adoptionmentioning
confidence: 99%